PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI PROVINSI KALIMANTAN TIMUR - . Hariati; . Ikhsan; Dwi Sepriono Nur (Jurnal Paradigma (JP), 2019)
In the era of regional autonomy, the development of micro, small and medium enterprises is one of the fields of government which is the mandatory authority that is handed over to the district/city governments. Then the local government has free to explore and develop the potential of micro, small and medium enterprises in accordance with the capabilities of each region. The efforts of industry, trade, cooperative and micro, small and medium enterprises in the form of growth in the business climate, growth of new business units, and the development of micro, small and medium enterprises have been carried out well by carrying out seven aspects of service ranging from production, marketing, capital, human resource development, institutional to information technology. Howover, there is still a need for another form of strategy that will strongly support all of these efforts, namely by forming a learning site that will be dedicated to fostering business actors in a sustainable and systematic manner. Keywords: micro, small and medium enterprises, development, businessmen.